2012
DOI: 10.1590/s0004-27302012000600001
|View full text |Cite
|
Sign up to set email alerts
|

Disfunção hipotalâmica na obesidade

Abstract: SUMÁRIOA obesidade, definida como o acúmulo excessivo ou anormal de gordura que pode causar dano à saúde do indivíduo, é considerada atualmente um dos principais problemas de saúde pública. Resulta de um desequilíbrio entre a ingestão alimentar e o gasto corporal de energia. O controle do balanço energético de animais e seres humanos é realizado pelo sistema nervoso central (SNC) por meio de conexões neuroendócrinas, em que hormônios periféricos circu lantes, como a leptina e a insulina, sinalizam neurônios es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 97 publications
0
6
0
2
Order By: Relevance
“…According to our data, patients with NF1 had a lower chance of having a high FBG level compared with non-NF1 controls. Although data from animal studies have indicated that neurofibromin plays a role in regulating functions of the hypothalamus and pituitary gland (28) , which are involved in body energy balance (29) , it is unclear whether neurofibromin deficiency could be responsible for the reduced FBG level in individuals with NF1.…”
Section: Discussionmentioning
confidence: 99%
“…According to our data, patients with NF1 had a lower chance of having a high FBG level compared with non-NF1 controls. Although data from animal studies have indicated that neurofibromin plays a role in regulating functions of the hypothalamus and pituitary gland (28) , which are involved in body energy balance (29) , it is unclear whether neurofibromin deficiency could be responsible for the reduced FBG level in individuals with NF1.…”
Section: Discussionmentioning
confidence: 99%
“…In the arcuate nucleus, leptin activates a subpopulation of neurons expressing proopiomelanocortin (POMC), while inhibiting neurons that synthesize Agouti-related protein (AgRP) and neuropeptide Y (NPY). This action leads to increased production of α-melanocyte stimulating hormone (α-MSH), which, in turn, is able to stimulate TRH expression by hypothalamic neurons by binding to the melanocortin 4 receptor (MC4-R) [64,65]. , and fT4 concentrations between the obese and normal weight group (baseline).…”
Section: Hyperleptinemiamentioning
confidence: 99%
“…Na auriculoterapia qualquer alteração em um determinado orgão ou parte do corpo pode ser detectada ou tratada pelo pavilhão auditivo, isso se dá pela grande quantidade de ramificações nervosas derivadas dos nervos espinhais e cranianos que ligam os pontos auriculares a regiões cerebrais 11 . É nesse contexto que a auriculoterapia tem efeito na obesidade, pois atua no controle homeostático do balanço energético ocasionado por esta disfunção 24 .…”
Section: Discussionunclassified